Pengolahan Sampah Organik Menjadi Biobriket Sebagai Energi Terbarukan - G M Saragih; Marhadi Marhadi; Yulia Defriati (Universitas Batanghari Jambi, 2020)
One of the uses of organic waste is processing it into biomass briquettes which can later be used as energy. Organic waste received is dry organic waste such as dry leaves, dry twigs, inorganic waste such as plastic waste which can be used as an adhesive in making waste biobriquettes. The purpose of processing organic and inorganic waste into energy is to benefit from the waste in the city of Jambi. The benefit obtained is to reduce waste which can be used as energy. The kerosene to LPG conversion program has resulted in a rapid increase in LPG consumption which domestic production cannot meet. This causes LPG imports to increase rapidly, so that if in 2007 the volume of LPG imports was still at 137 thousand tons, in 2011 it increased to 1,992 thousand tons or an increase of almost 15 times (Outlook Energi Indonesia 2013). The highest calorific value with the optimum composition is found in biobriquette sample 3 with a variation of the composition of 75% organic waste: 5% inorganic waste: 10% water: 10% glue, which is 19361 J / gr. The lowest ash content with the optimum composition was found in sample 3 with a variation of the composition of 75% organic waste: 5% inorganic waste: 10% water: 10% glue, namely 5.06%. The lowest water content with the optimum composition is found in sample 1 and sample 2 with a water content of 0.92%, this is already in accordance with SNI for biobriquettes. The lowest CO content with the optimum composition is found in the biobriquette sample 1 with a variation of the organic composition of 85%: 5% inorganic: 5% water: 5% glue, which is 60.33 μg/Nm3.